Extramedullary nasal plasmacytoma: Literature review and a rare case report - Corvo,Marco Antonio dos Anjos (2013)
INTRODUCTION: Extramedullary plasmacytoma is a plasma cell tumor that grows within any of the soft tissues of the organism. Similar to all plasmacytic dyscrasia, the disease is extremely rare. AIM: This study reports a case of an extramedullary plasmacytoma of the nasal cavity and provides a literature review on the topic. CASE REPORT: A 51-year-old woman presented at our tertiary university hospital with a 6-month history of progressive nasal obstruction, predominantly to the right side, and self-limiting epistaxis. Examination revealed a large pale-reddish tumor within the right nasal cavity. Anatomopathological analysis showed features consistent with a plasmacytoma diagnosis, which was subsequently confirmed by immunohistochemical techniques. Further assessment revealed the solitary nature of the condition, consistent with extramedullary plasmacytoma. Radiotherapy was initiated, which led to partial regression of the symptoms. The tumor was surgically removed by using a mid-facial degloving approach. The patient evolved with a naso-oral fistula and underwent 3 corrective surgeries. No evidence of associated systemic disease was found after 5 years of follow-up. CONCLUSIONS: This case report, which describes a rare tumor of the nasal cavity, is expected to improve the recognition and referral of this condition by ear, nose, and throat (ENT) specialists for multidisciplinary management and long-term follow-up.